Enhancing Customer Retention Through Satisfaction: The Impact of Service Quality and Hedonic Value in Online Auction KOI Nusantara Company - Supriadi, Bambang; Laksana, Yosanta Ardhi; Sugito, Pudjo; Syamsuddinnor, S (Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to describe and analyze the eff ect of hedonic value and service quality on customer retention and satisfaction, analyze the eff ect of customer satisfaction on customer retention, and analyze the eff ect of hedonic value and service quality on customer retention through customer satisfaction at KOI Nusantara online auction company. The research location is KOI Nusantara, an online auction company. The data analysis technique in this study uses Structural Equation Modeling (SEM) analysis. The research fi ndings show that hedonic value and service quality create positive experiences and increase satisfaction and customer trust. Whereas service quality has a greater eff ect on retention, hedonic value has a greater eff ect on customer satisfaction. Furthermore, customer satisfaction, especially from product reuse, has a greater eff ect on customer retention. Both service quality and hedonic value will be more eff ective in increasing retention if customer satisfaction is supported. The research contribution is strategic recommendations for online auction companies, such as KOI Nusantara, to improve service quality and increase customer retention. In addition, it is important to create hedonic value to increase customer satisfaction, which ultimately strengthens customer loyalty. The fi ndings provide new insights into the priorities of customer experience management. They can be used to design more eff ective service and marketing strategies in the online auction industry.